1973
DOI: 10.1139/f73-269
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures Selected Seasonally by Four Fishes from Western Lake Erie

Abstract: When four species of fish were taken from western Lake Erie in each of four seasons and held usually for less than 7 days at ambient lake temperatures, the temperatures they selected during 2–3 days in a horizontal temperature gradient differed seasonally. The differences were largely attributable to the conditions at which the fish had been acclimatized in the lake, and were modified by acclimation during 2–3 days in the gradient.The selected temperatures provided insights into the temperatures that might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The function of this behavior in nature is unknown. No seasonal differences were found in the selected temperatures of damselfish and butterfly&h. When compared to the temperate locations where seasonal variations in selected temperatures have been found (Sullivan & Fisher 1953, Barans & Tubb 1973 seasonal changes in temperature preferred by Hawaiian fishes would seem likely to be smaller.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The function of this behavior in nature is unknown. No seasonal differences were found in the selected temperatures of damselfish and butterfly&h. When compared to the temperate locations where seasonal variations in selected temperatures have been found (Sullivan & Fisher 1953, Barans & Tubb 1973 seasonal changes in temperature preferred by Hawaiian fishes would seem likely to be smaller.…”
Section: Resultsmentioning
confidence: 87%
“…Adults occur in deeper, cooler water (Helfrich 1958, Hobson 1972, both on the bottom and in mid-water feeding schools. The young of three of five freshwater species (Barans & Tubb 1973, McCauley & Read 1973) selected warmer temperatures than the adults. This preference for warmer water by juveniles is consistent with their habitat preference.…”
Section: Resultsmentioning
confidence: 99%
“…Season can have a major impact on temperatures selected, possibly through seasonal shifts in metabolic rate (Sullivan & Fisher 1953, Fry & Hochachka 1970, Barans & Tubb 1973. Another factor which may affect the reaction of plaice on the Grand Banks to temperature is avoidance of freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Vigg et al (1991) suggested that many factors influence consumption rates of smallmouth bass, but water temperature was considered the single most important factor. Smallmouth bass exist in water temperatures ranging from 12 to 31°C (Ferguson 1958;Barans and Tubbs 1973) and the final preferendum is approximately 28°C (Coble 1975). Smallmouth bass become active in water temperatures >10°C (Munther 1970) and begin actively feeding at approximately 15°C (Carlander 1977).…”
Section: Consumption Of Fall Chinook Salmonmentioning
confidence: 99%